STROKE: THE PRIORITY OF THE PRIMARY PREVENTION IS NECESSARY - A. T. Bykov; T. N. Malyarenko; Yu. E. Malyarenko; O. L. Eroshenko (Медицинский вестник Юга России, 2014)
Basing on the opinion of some foreign researchers and clinicians, we can state that the early prophylaxis of cerebrovascular incidents plays an essential role. We have also come to a conclusion that in preventive anti-stroke programs, especially for elderly people, systemic influences should prevail.